Time Management and its Application in Teaching Recitation and Tajweed, Refinement, in the Faculty of Sharia’a at the University Of Jordan - Al-Jaghul, Faten AbduRaheem Saleh; Abu Suailiq, Sanaa Suleiman Salama (Dirasat: Shari’a and Law Sciences, 2024)
Objectives: This research addresses the applications of the time management skill, its importance, and its investment in teaching the different subjects of recitation and memorization, each according to its vocabulary during the semester. Furthermore, the research aims at providing researchers and educators with insights into leveraging this skill in other university courses. Methods: The research followed the inductive, descriptive, and experimental approach by extrapolating, describing, and experimenting with applications of the time management skill, and showing how to invest and implement it in the classroom lecture and during the teaching process. Results: The study has identified proposed methods, practical applications, and guidance for both teachers and students, along with factors and enhancers for leveraging time management in successfully teaching recitation and Tajweed subjects. It illustrates how students can master the components of recitation and memorization subjects, refine their skills, and progress from the learning to the teaching stage, achieving the desired objectives of the courses (proficient memorization and accurate recitation). Additionally, the study highlights the importance of utilizing this skill in teaching all academic courses for maximum benefit. Conclusion: The study concludes on the necessity of benefiting from time management strategies and implementing them in the practical and educational reality of recitation and memorization subjects. It emphasizes the importance of innovating effective methods for time management in teaching, actively engaging with these applications in the teaching process, and recognizing their positive impact on education.